PENERAPAN CORPORATE GOVERNANCE DENGAN MENGGUNAKAN BALANCE SCORECARD PADA BANK MANDIRI JEMBER - Nugraheni, Ponti Primastuti Aulia (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: Good corporate governance is a barometer of for a company accountability. A poor corporate governance implementation is presumed as one of the causes of various corporate financial business scandals. Banking companies deal directly with the provision of goods and services to meet the wants and needs of the community. In this case, the community is the customer that must be served well in order to meet their satisfaction by applying a good organizational management mindset to improve the customer (community) satisfaction. Applying the Balanced Scorecard (BSC) approach, banks will be able to explain their mission to the community, identify the indicators of public satisfaction more transparently, objective, and measurable, and identify the work processes and the quality of human resources needed to achieve their mission and vision. In the implementation process, the banking activities will produce a community-oriented strategic management system. Keywords: Corporate Governance, Bank, BSC.